Fiber Bragg Grating (FBG) Sensors in a High-Scattering Optical Fiber Doped with MgO Nanoparticles for Polarization-Dependent Temperature Sensing - Molardi, Carlo; Tiago, Paixao; Beisenova, Aidana; Min, Rui; Paulo, Antunes; Marques, Carlos; Blanc, Wilfried; Tosi, Daniele (APPLIED SCIENCES-BASEL, 2019)
The characterization of Fiber Bragg Grating (FBG) sensors on a high-scattering fiber, having the core doped with MgO nanoparticles for polarization-dependent temperature sensing is reported. The fiber has a scattering level 37.2 dB higher than a single-mode fiber. FBGs have been inscribed by mean of a near-infrared femtosecond laser and a phase mask, with Bragg wavelength around 1552 nm. The characterization shows a thermal sensitivity of 11.45 pm/degrees C. A polarization-selective thermal behavior has been obtained, with sensitivity of 11.53 pm/degrees C for the perpendicular polarization (S) and 11.08 pm/degrees C for the parallel polarization (P), thus having 4.0% different sensitivity between the two polarizations. The results show the inscription of high-reflectivity FBGs onto a fiber core doped with nanoparticles, with the possibility of having reflectors into a fiber with tailored Rayleigh scattering properties.
Keywords: Fiber Bragg Grating (FBG); Rayleigh scattering; enhanced backscattering fiber; polarization-sensitive device